Power narrowing: counteracting Doppler broadening in two-color transitions. (9th October 2019) - Finkelstein, Ran; Lahad, Ohr; Michel, Ohad; Davidson, Omri; Poem, Eilon; Firstenberg, Ofer
Abstract: Doppler broadening in thermal ensembles degrades the absorption cross-section and the coherence time of collective excitations. In two photon transitions, it is common to assume that this problem becomes worse with larger wavelength mismatch. Here we identify an opposite mechanism, where such wavelength mismatch leads to cancellation of Doppler broadening via the counteracting effects of velocity-dependent light-shifts and Doppler shifts. We show that this effect is general, common to both absorption and transparency resonances, and favorably scales with wavelength mismatch. We experimentally confirm the enhancement of transitions for different low-lying orbitals in rubidium atoms and use calculations to extrapolate to high-lying Rydberg orbitals. These calculations predict a dramatic enhancement of up to 20-fold increase in absorption, even in the presence of large homogeneous broadening. More general configurations, where an auxiliary dressing field is used to counteract Doppler broadening, are also discussed and experimentally demonstrated. The mechanism we study can be applied as well for rephasing of spin waves and increasing the coherence time of quantum memories.